Seroprevalences of antibodies against ToRCH infectious pathogens in women of childbearing age residing in Brazil, Mexico, Germany, Poland, Turkey and China. (30th October 2020) - Warnecke, J. M.; Pollmann, M.; Borchardt-Lohölter, V.; Moreira-Soto, A.; Kaya, S.; Sener, A. G.; Gómez-Guzmán, E.; Figueroa-Hernández, L.; Li, W.; Li, F.; Buska, K.; Zakaszewska, K.; et al.
Abstract: Determination of antibodies against ToRCH antigens at the beginning of pregnancy allows assessment of both the maternal immune status and the risks to an adverse pregnancy outcome. Age-standardised seroprevalences were determined in sera from 1009 women of childbearing age residing in Mexico, Brazil, Germany, Poland, Turkey or China using a multiparametric immunoblot containing antigen substrates for antibodies against Toxoplasma gondii, rubella virus, cytomegalovirus (CMV), herpes simplex viruses (HSV-1, HSV-2), Bordetella pertussis, Chlamydia trachomatis, parvovirus B19, Treponema pallidum and varicella zoster virus (VZV). Seroprevalences for antibodies against HSV-1 were >90% in samples from Brazil and Turkey, whereas the other four countries showed lower mean age-adjusted seroprevalences (range: 62.5–87.9%). Samples from Brazilian women showed elevated seroprevalences of antibodies against HSV-2 (40.1%), C. trachomatis (46.8%) and B. pertussis (56.6%) compared to the other five countries. Seroprevalences of anti- T. gondii antibodies (0.5%) and anti-parvovirus B19 antibodies (7.5%) were low in samples from Chinese women, compared to the other five countries. Samples from German women revealed a low age-standardised seroprevalence of anti-CMV antibodies (28.8%) compared to the other five countries. These global differences in immune status of women in childbearing age advocate country-specific prophylaxis strategies to avoid infection with ToRCH pathogens.